P Penetapan Kadar Flavonoid Total Dan Aktivitas Antioksidan Daun Karinat (Rubus moluccanus L.) - Sadlia, Fitri; Hakim, Ali Rakhman; Saputri, Rina; Rohama, Rohama (LPPM Universitas Sari Mulia, 2024)
Background: This environmental exposure triggers the formation of free radicals, also known as reactive oxygen species (ROS). Apart from being caused by exogenous factors, free radicals are also formed naturally through physiological cell metabolism. Free radicals that are not handled will have a negative impact on humans, including abnormal changes that affect certain genes in the body that cause cancer. Carinate leaf extract is also qualitatively proven to contain flavonoid compounds based on Thin Layer Chromatography results which have potential as antioxidants.Objective: This study generally aims to determine the total flavonoids and antioxidant activity in carinate leaf extract (Rubus moluccanus L) leaf extractMethods: This research method is a laboratory experiment with a true-experimental research design using a post test only control group design. The control group in this study was quercetin (DPPH) and variations in the concentration of ethanol extract of carinate leaves as the treatment group.Results: The results explained that carinate leaf extract has a total flavonoid content of 143.8 mg/Qe/g with an average IC50 value of 1,32 ppm which means the antioxidant activity of carinate leaves is very strong and better than quercetin with an average IC50 value of 2,19 ppm. T Independent Sample analysis results obtained of 0.000 which that there is a significant difference in antioxidant activity between carinate leaves and quercetin.Conclusion: Carinate leaves have very strong antioxidant activity so that carinate leaves can be utilized as antioxidants.